Interferometric technique for measuring broadband ultrashort pulses at the sampling limit. - Kosik, E; Radunsky, A; Walmsley, I; Dorrer, C (2005)
We present a new technique for measuring ultrashort optical pulses by use of spectral phase interferometry for direct electric-field reconstruction that is suitable for large bandwidth pulses. The method does not require generation of a replica of the pulse to be measured and encodes the spectral phase information in a spatial interference pattern. A major advantage of this method is that the spectral sampling saturates the Whittaker-Shannon bound. Moreover, the technique allows for the characterization of some types of space-time coupling. An experimental demonstration of the technique is presented.